Robotic Competitions to Design Future Transport Systems: The Case of JRC AUTOTRAC 2020. Issue 2 (February 2023) - Ciuffo, Biagio; Makridis, Michail; Padovan, Valter; Benenati, Emilio; Boriboonsomsin, Kanok; Chembakasseril, Mamen Thomas; Daras, Petros; Das, Viswanath; Dimou, Anastasios; Grammatico, Sergio; Hartanto, Ronny; Hoelscher, Malte; et al.
Vehicle automation and connectivity bring new opportunities for safe and sustainable mobility in urban and highway networks. Such opportunities are however not directly associated with traffic flow improvements. Research on exploitation of connected and automated vehicles (CAVs) toward a more efficient traffic currently remains at a theoretical level, and/or based on simulation models with limited reliability. Furthermore, testing CAVs in the real world is still costly and very challenging from an implementation perspective. A possible alternative is to use automated robots. By designing and testing both the low- and the high-level controllers of CAVs, it is indeed possible to reach a better understanding of the challenges that future vehicles will need to face. Robotic applications can effectively test these challenges within a wide variety of research communities—for example, via robotic competitions. Along this direction, the Joint Research Centre has organized the first European robotic traffic competition for automated miniature vehicles. Each team participated with four robots and was judged based on a set of indicators that assess the collective behaviors of the vehicles. Results show the suitability of the methodology with different teams proposing completely different approaches to deal with the challenge and thus achieving different results. Future competitions may further raise awareness about the possibility of using CAVs to improve traffic and to engage with a broader community to design systems that are really capable of achieving this goal.